2015
DOI: 10.1136/bmj.h4978
|View full text |Cite
|
Sign up to set email alerts
|

Suicide risk assessment and intervention in people with mental illness

Abstract: Suicide is the 15th most common cause of death worldwide. Although relatively uncommon in the general population, suicide rates are much higher in people with mental health problems. Clinicians often have to assess and manage suicide risk. Risk assessment is challenging for several reasons, not least because conventional approaches to risk assessment rely on patient self reporting and suicidal patients may wish to conceal their plans. Accurate methods of predicting suicide therefore remain elusive and are acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
188
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(201 citation statements)
references
References 145 publications
(121 reference statements)
3
188
0
7
Order By: Relevance
“…Consistent with findings from the general population, depressive and anxiety disorders were the strongest determinants of suicidal ideation during the acute phase of ACS [3,27]. Moreover, two previous studies with heterogeneous evaluation points after ACS also found similar results [9,10].…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with findings from the general population, depressive and anxiety disorders were the strongest determinants of suicidal ideation during the acute phase of ACS [3,27]. Moreover, two previous studies with heterogeneous evaluation points after ACS also found similar results [9,10].…”
Section: Discussionsupporting
confidence: 88%
“…There are several possible explanations for the increased risk of suicide associated with diabetes. Depressive symptoms and suicidal ideation are common in patients with diabetes, both of which are associated with increased risk of completed suicide (10,11,79). Apart from depression, other mental health problems are also common in diabetes patients, which can also lead to increased risk of suicide (80,81).…”
Section: Discussionmentioning
confidence: 99%
“…Incremental improvement in risk stratification might occur if there is identification of previously unknown risk factors, 23 or new ways of combining established risk factors with methods derived from artificial intelligence research. 24 But to be useful to a clinician, new methods of suicide risk stratification would need to be several orders of magnitude more powerful than the existing methods.…”
Section: Is Ongoing Research Likely To Provide Relevant Evidence?mentioning
confidence: 99%